AN EVALUATION OF THE EFG GROWTH MODEL IN ITS CAPACITY TO PREDICT AMINO ACID REQUIREMENTS IN BROILERS - Indarsih, B.; Pym, R.A.E. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
An experiment imposing the multi continuous phase feeding was carried out to evaluate the EFG(Emman, Fisher and Gous) Growth Model in its capacity to predict amino acid requirements in broilers.Birds were fed using blended summit (247.91g/kg CP, 3200 kcal of ME /kg) and dilution (166.26 g/kgCP, 3200 kcal of ME g/kg ) diets and offered to 2-4 or 8 phases. Two hundred male day-old broilerchicks of two commercial strains (A=Ingham and B = Steggles) were used. The predicted responseswere greater than the observed both gain (g/d) and feed intake (g/d). The discrepancy between theobserved and predicted gain in the strain A and B birds, showed a different pattern, with a markeddifference during the early growing period, with a degree of convergence in the late growing period forthe strain A but the reverse picture for the strain B. This shows that strain characterization is notaccurate due to an inadequate definition of the genotypes by the model. Non agreement betweenpredicted and determined gain and feed intakes provided little benefit in moving towards a morefrequent change in diet to accommodate predicted growth-related changes in amino acid requirements.